AUTHENTIC-BASED ASSESSMENT IN ENGLISH LANGUAGE LEARNING: A STUDY ON NON-ENGLISH MAJOR STUDENTS' DESCRIPTIONS OF DAILY ACTIVITIES - Muhsin, Muh arief (IJEE (Indonesian Journal of English Education), 2024)
This study investigates the quality of language use among non-English major students in Indonesia through authentic assessment of English language learning. Five students from diverse majors were selected as subjects, and their written descriptions of daily activities during the holiday were analyzed. The assessment criteria included grammar and syntax, vocabulary, clarity and precision, organization and cohesion, conventions and mechanics, audience and purpose alignment, as well as creativity and style. Data analysis followed the framework proposed by Miles and Huberman, involving data collection, sorting, coding, pattern identification, interpretation, and verification. The findings revealed varied levels of language proficiency among the students. Some essays exhibited accurate grammar and sentence structure, while others contained recurring errors, particularly in subject-verb agreement and sentence construction. Vocabulary usage ranged from adequate to descriptive, though specific essays required more precise word choices. Clarity and precision were generally observed, though transitions between paragraphs often needed improvement. Organization and cohesion were inconsistent, with some essays lacking clear structure and logical flow. While most students adhered to writing conventions, minor errors in spelling and punctuation were noted. Audience and purpose alignment were generally effective, and creativity was evident, although some essays displayed underdeveloped stylistic expression. Overall, this research offers valuable insights into the language proficiency of non-English major students and provides recommendations for improving writing skills through authentic assessment methods. Future studies could focus on implementing the feedback from these assessments to enhance the quality of students' written descriptions.